DESIGNING A BUSINESS ENGLISH ESP COURSE FOR MARKETING AND SALES STUDENTS: A NEEDS-BASED APPROACH: DESIGNING A BUSINESS ENGLISH ESP COURSE FOR MARKETING AND SALES STUDENTS: A NEEDS-BASED APPROACH - Madaminova, Nilufar (Журнал иностранных языков и лингвистики, 2025)
technology, research, and education. Its status as a lingua franca has led to increased demand for ESP, particularly in sectors where precise and context-based communication is essential. ESP diverges from general English in that it is tailored to the specific language functions and vocabulary required in a learner’s field of study or profession